Successful assisted conception in a case of recalcitrant chronic urticaria treated with omalizumab: A case report - Dg Marshitah Pg Baharuddin; Ehab Helmy Abdel Malek Fahmy; Mohd Nazri Mohd Daud; Mohsen MA Abdelhafez; Ling Yien Hii; Sook Yee Michelle Voo; Wen Foong Tan (Medical Journal of Malaysia Case Reports (MJM Case Reports), 2025)
Chronic urticaria (CU) is a debilitating disease characterized by recurrent wheals, angioedema, or both, lasting for at least six weeks. Although self-limiting, it remains a challenging condition to manage, particularly in patients with specific comorbidities. We report the case of a 39-year-old woman with recalcitrant CU and polycystic ovarian syndrome (PCOS), along with a history of adverse obstetric events. Her CU was successfully treated with subcutaneous omalizumab, providing excellent symptom control and enhancing her quality of life. Subsequently, she underwent an uneventful assisted reproduction technology (ART) procedure with a meticulously timed, resulting in the birth of healthy twins. This case highlights the role of omalizumab in treating recalcitrant CU during the preconception period and its continuation throughout pregnancy. It also underscores the importance of a comprehensive multidisciplinary approach in achieving a successful outcome.